2008
DOI: 10.1111/j.1742-481x.2007.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure transduction to the thoracic cavity during topical negative pressure therapy of a sternotomy wound

Abstract: The present study was performed to examine pressure transduction to the thoracic cavity during topical negative pressure (TNP) therapy of a sternotomy wound. Seven pigs underwent median sternotomy. Pressure transduction catheters were placed on the anterior surface of the heart (under the foam), in the pericardium (under the heart), in the left pleura and in the oesophagus at the level of the heart. The wound was sealed as for TNP therapy. The vacuum source was set to deliver negative pressures between -50 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Previous publications have reported on the transmission of negative pressure to the wound bed. 12,14,15 Pressure transduction to the tissue from the vacuum source is dependent on adequate drainage tubes and a wound filler that is a material that does not inhibit pressure transduction. It has been shown that interface dressings influence the delivery of topical negativepressure therapy to the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have reported on the transmission of negative pressure to the wound bed. 12,14,15 Pressure transduction to the tissue from the vacuum source is dependent on adequate drainage tubes and a wound filler that is a material that does not inhibit pressure transduction. It has been shown that interface dressings influence the delivery of topical negativepressure therapy to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,15 Also, in complicated wounds, such as in the thoracic cavity, all spaces that are not in direct contact with the wound filler will not be reached by the negative pressure. 15 The wound model used in the current study is a superficial wound in which the entire wound bed has contact with the wound-filling material. This is presumably why the wound bed pressure was similar to the negative pressure set on the vacuum source pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation complied with the ‘Guide for the Care and Use of Laboratory Animals' as recommended by the US National Institutes of Health and published by the National Academies Press (1996). Anesthesia and surgery were performed as described earlier (11).…”
Section: Methodsmentioning
confidence: 99%
“…2,[17][18][19][20] NPWT was originally described for chronic wounds in people but applications for a variety of wounds and surgical situations are now reported, mainly in case series and clinical reviews. 21 The high rate of clinical success and relative ease of application of NPWT have encouraged adaptation in compromised flaps, [22][23][24][25] free skin grafts, [26][27][28][29] postoperative sternal incisional infection and mediastinitis, [30][31][32][33][34] perineal, urologic, and gynecologic wounds, 35,36 as well as for cytotoxic sloughs, 37 abdominal wall defects and drainage, [38][39][40][41] and burns. 42,43 Reduced overall treatment cost and shortened hospitalization have been documented with NPWT.…”
mentioning
confidence: 99%